2009
DOI: 10.2174/138945009789108747
|View full text |Cite
|
Sign up to set email alerts
|

Inhalational Anesthetics in Acute Severe Asthma

Abstract: Acute severe asthma is characterized by a state of airway inflammation and increased bronchiolar smooth-muscle tone that leads to increased resistance to expiration and lung hyperinflation. Despite the better knowledge of its pathophysiology, the incidence and severity of asthma in the last twenty years is increased worldwide, although with significant age and geographic variation. As a result, the number of patients requiring more intensive medical therapy has also increased. In the most severe cases, often r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…It has been suggested that halogenated gas ensures adequate ventilation by decreasing airway resistance [25]. While the one patient who was treated with halogenated gas in our study had a good outcome, the evidence for the efficacy of this technique is based only on small case reports [26]. Indications for this treatment, which is not included in recent recommendation [10], have yet to be clearly defined.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…It has been suggested that halogenated gas ensures adequate ventilation by decreasing airway resistance [25]. While the one patient who was treated with halogenated gas in our study had a good outcome, the evidence for the efficacy of this technique is based only on small case reports [26]. Indications for this treatment, which is not included in recent recommendation [10], have yet to be clearly defined.…”
Section: Discussionmentioning
confidence: 78%
“…All patients were known to have asthma. Atopy was found in 87% of the patients, and the diagnosis of asthma was made 21 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] years earlier. A quarter of the patients had a previous episode of ASA that required IMV.…”
Section: Resultsmentioning
confidence: 99%
“…Though volatile anesthetics have been shown to be effective in acute asthmatic bronchospasm, data on prolonged application is rare [11]. A common concern against the prolonged use of volatile anesthetics is their potential harm to renal function.…”
Section: Discussionmentioning
confidence: 99%
“…All of the available VAs, halothane, isoflurane, sevoflurane, and desflurane, have been used to treat refractory SA . However, given that desflurane has been shown to increase airway resistance in children with high airway susceptibility , caution should be taken when considering its use in the pediatric patient with SA.…”
Section: Treatmentmentioning
confidence: 99%